Isolation and cultivation of Botryococcus braunii Kützing from Northern Thailand - Sunisa Boonma (2018)
Botryococcus braunii were isolated from eight natural water resources in Northern Thailand. The effect of media: modified CHU 13 medium (pH 6. 7), Jaworski's medium (pH 7. 0) and CA medium, on B. braunii isolation was compared. It was found that CA was suitable for B. braunii isolation. B. braunii HM5 isolated from the reservoir of the Hill Tribe Museum, Chiang Mai, showed the highest growth rate. The optimal condition for this strain was at ambient temperatures (26. 5-32. 5°C) in CA medium, supplemented with 10% CO 2 , at pH 7. 2 which provided 6. 31 g·L -1 of biomass and 41. 74% hydrocarbon accumulation.